2005
DOI: 10.1097/01.mlg.0000175538.89627.0d
|View full text |Cite
|
Sign up to set email alerts
|

Oropharyngeal Complications Of Suspension Laryngoscopy: A Prospective Study

Abstract: SL carries a higher risk for lingual and glossopharyngeal nerve injuries than previously recognized. All of these complications were temporary. On the basis of comparison with historic data, SL by gallows suspension technique may pose a lower risk of dental injuries. This information should be used to improve preoperative SL patient education and informed consent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
81
1
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(91 citation statements)
references
References 17 publications
2
81
1
4
Order By: Relevance
“…This problem was related to compression and ischemia of local tissue and a local segment of nerves. Complications from suspension laryngoscopy involving problems with tongue mobility caused by temporary lingual nerve injury in suspension laryngoscopy have also been reported [12,13]. It was attributed to the prevalent use of large laryngoscopes and long operative suspension time in micro-phonosurgery.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This problem was related to compression and ischemia of local tissue and a local segment of nerves. Complications from suspension laryngoscopy involving problems with tongue mobility caused by temporary lingual nerve injury in suspension laryngoscopy have also been reported [12,13]. It was attributed to the prevalent use of large laryngoscopes and long operative suspension time in micro-phonosurgery.…”
Section: Discussionmentioning
confidence: 95%
“…8590B is one of the commonly used laryngoscope in China. Rosen et al [12] reported that the size of the laryngoscope was found to be a risk factor for post-microlaryngoscopy complication. We thought that the pressure is related to the size of the laryngoscope, small size with lower pressure and large size with higher pressure.…”
Section: Discussionmentioning
confidence: 98%
“…tooth extraction [11] or uvulopalatopharyngoplasty [12], MLS [4 Á6]) or even intubation, only a few studies have systematically investigated the occurrence of taste disorders after MLS [1,9,13]. With one exception [13], these studies have not measured taste function, but solely asked the patients whether they experienced taste dysfunctions [1,3,9].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies [1,3,9] and case reports [2,4 Á6] found transient qualitative taste disorders (dysgeusia, parageusia, metallic taste) to occur in approximately 10% of MLS patients. The authors speculated that these transient taste disorders were due to tongue compression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation